Peritoneal dialysis associated non tuberculous mycobacterial peritonitis at a tertiary care hospital in the UK. (January 2023) - Gokani, Karishma; Davda, Pretin; Dedicoat, Martin J.; Kamesh, Lavanya; David, Miruna D.
Highlights: Time to culture NTM organism ranged from 2 to 27 days. Consider prolonged culture to 14 days in culture negative peritonitis. We recommend 6 week mycobacterial culture where NTM infection suspected. Abstract: Background: Peritonitis remains a significant cause of peritoneal dialysis (PD)-associated morbidity, and technique failure. Non-tuberculous mycobacteria (NTM), commonly found in the environment (soil and water sources), are a rare cause of PD peritonitis, particularly important to consider in culture negative peritonitis. Methods: Cases were identified via a search of the local microbiology laboratory database system between 01/01/2011 and 01/01/2020 at the Queen Elizabeth Hospital Birmingham, UK. Cases were identified by isolation of a Mycobacterium sp. other than Mycobacterium tuberculosis complex either from a PD exit site culture or from PD peritoneal fluid culture. We identified nine cases of peritonitis and one of isolated exit site infection (ESI). Results: Clinical presentation was similar to peritonitis caused by usual bacterial pathogens. Of the peritonitis cases, three were due to M. chelonae, three M. fortuitum, two M. abscessus and one M. chimera . The ESI was caused by M. fortuitum . The peritoneal fluid microscopy showed a neutrophil predominance. In 80 % of the cases in our cohort, the microorganism was identified from the culture of the first peritoneal dialysis (PD) fluid sample, however the time to identification from culture ranged from 2 to 27 days. All mycobacteria were grown from standard culture media, except for M. chimera which required a specialist mycobacterial liquid culture system. All cases of peritonitis underwent PD catheter removal with conversion to haemodialysis. Treatment length and antibiotic combinations varied significantly, with some cases being successfully treated with courses as short as 4 weeks. Significant antibiotic related side effects including hearing loss and QTc prolongation were noted. Conclusion: We would recommend extending standard microbiological cultures of culture negative peritonitis to 2 weeks and employing mycobacterial culture media incubated for 6–10 weeks as would be standard for mycobacterial investigations, prior to exclusion of NTM as a causative organism of peritonitis.